(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Numerous scientific research projects focused on the processing of apricots are being conducted in the Republic of Uzbekistan. Scientific research on apricot fruit processing in the Republic of Karakalpakstan has not been fully studied in a scientifically sound state. Considering that in our region, apricot trees are mainly grown in household plots, it is required to meet the population’s year-round demand for this product by producing processed apricot dried apricots, varenets, and other products.